The NK-3 tachykinin receptor agonist senktide elicits 5-HT-mediated behaviour following central or peripheral administration in mice and rats. - Stoessl, A; Dourish, C; Iversen, S (1988)
The behavioural effects of the selective NK-3 tachykinin receptor agonist senktide were studied following intracisternal and subcutaneous administration in rodents. Behavioural manifestations of 5-hydroxytryptaminergic stimulation, including head twitches (mice), wet dog shakes (rats), forepaw treading, flat body posture, hindlimb splaying and Straub tail, were seen following the intracisternal (0.01-1.2 nmol) or subcutaneous (0.1-2.4 mumol kg-1) administration of senktide in both species. We conclude that stimulation of NK-3 receptors stimulates 5-hydroxytryptaminergic pathways in rodent brain, and that senktide may cross the blood-brain barrier in biologically significant amounts.